Secure medical chatbot: leveraging encryption for patient data privacy - Oh, Terence Yuan Zhang (Nanyang Technological University, 2024)
In the digital era, providing accessible healthcare advice while ensuring patient data privacy has become a critical concern. This project introduces MediBot, a secure medical chatbot interface designed to offer patients reliable medical guidance using Large Language Models (LLMs), without compromising the confidentiality of their sensitive information. Recognizing the limitations and privacy risks associated with generic chatbots like ChatGPT—particularly regarding data handling and compliance with healthcare regulations—MediBot is developed as a dedicated platform tailored for hospital use.